Front-line Service Employees' Job Satisfaction in the Hospitality Industry: The Influence of Job Demand Variability and the Moderating Roles of Job Content and Job Context Factors. (November 2014) - Chiang, Flora F. T.; Birtch, Thomas A.; Cai, Zhenyao
A study of 302 front-line employees in three 5-star Hong Kong hotels found that high job demand variability diminished their job satisfaction. However, adding discretion to the job content and improving rewards and training as part of the job context resources and support were found to moderate the negative effects of high job demand variability on the employees' job satisfaction. The importance of service discretion is particularly intriguing for these employees, since their hotels' current cultural approach is to require supervisory approval for deviations from standard practice. This study draws on the job demands–control (JD-C) model to incorporate socio-psychological characteristics of customer service positions in the analysis of employees' job satisfaction.